The Surface Oxidation States of Copper Nanoparticles Generated by Ligand-Mediated Laser Ablation - Mulder, Ashley Jade (Curtin University, 2017)
Copper nanoparticles (CuNPs) generated by Laser Ablation Synthesis in Solution (LASiS) were encapsulated and stabilised by a variety of ligands in solution. The encapsulation ligands where chosen to utilise the N-donor binding ability to the CuNPs. This facilitated the oxidative control of the CuNPs, controlling the surface plasmon resonance of the CuNPs. Exploitation of this oxidative control has implications for various nanotechnological applications.